Răspuns :
a = 1, 5
b = 0,2
a ) 2a + 3b = 2 * 1,5 + 3 * 0,2 = 3 + 0,6 = 3,6
b) a - 2b = 1,5 - 2 * 0,2 = 1,5 -0,4 = 1,1
c) a^2 - b^2 = 2,25 - 0,04 = 2,21
d) 10a - b : 2 * 10 = 10 * 1,5 - 0,2 : 2 * 10 = 15 - 0,1 * 10 =15 - 1 = 14
b = 0,2
a ) 2a + 3b = 2 * 1,5 + 3 * 0,2 = 3 + 0,6 = 3,6
b) a - 2b = 1,5 - 2 * 0,2 = 1,5 -0,4 = 1,1
c) a^2 - b^2 = 2,25 - 0,04 = 2,21
d) 10a - b : 2 * 10 = 10 * 1,5 - 0,2 : 2 * 10 = 15 - 0,1 * 10 =15 - 1 = 14
a = 1, 5
b = 0,2
2a + 3b = 2 * 1,5 + 3 * 0,2 = 3 + 0,6 = 3,6
a - 2b = 1,5 - 2 * 0,2 = 1,5 -0,4 = 1,1
a^2 - b^2 = 2,25 - 0,04 = 2,21
10a - b : 2 * 10 = 10 * 1,5 - 0,2 : 2 * 10 = 15 - 0,1 * 10 =15 - 1 = 14 corona?
b = 0,2
2a + 3b = 2 * 1,5 + 3 * 0,2 = 3 + 0,6 = 3,6
a - 2b = 1,5 - 2 * 0,2 = 1,5 -0,4 = 1,1
a^2 - b^2 = 2,25 - 0,04 = 2,21
10a - b : 2 * 10 = 10 * 1,5 - 0,2 : 2 * 10 = 15 - 0,1 * 10 =15 - 1 = 14 corona?